140 likes | 306 Views
Simplifying Boolean Expressions. Boolean Operators (T/F). Boolean Operators (1/0). Boolean Operators Symbols. Simplifying Boolean Expressions. Commutative laws A + B = B + A A · B = B · A Associative laws A + (B + C) = (A + B) + C A · (B · C) = (A · B) · C Distributive laws
E N D
Simplifying Boolean Expressions • Commutative laws A + B = B + A A · B = B · A • Associative laws A + (B + C) = (A + B) + C A · (B · C) = (A · B) · C • Distributive laws A · (B + C) = A · B + A · C A + (B · C) = (A + B) · (A + C)
Simplifying Boolean Expressions • Tautology laws A · A = A A + A = A A + ~A = 1 A · ~A = 0 • Absorption Law A + (A · B) = A A · (A + B) = A
Simplifying Boolean Expressions • Identities 0 · A = 0 0 + A = A A + 1 = 1 1 · A = A A = A • Complement A + ~A · B = A + B
Examples • A + A + A + A = A Using the Tautology law
A Bigger Example Simplify ~A · B + A · ~B + ~A · ~B ~A · B + A · ~B + ~A · ~B ~A · B + (A · ~B + ~A · ~B) Associative ~A · B + (~B · (A + ~A)) Distributive ~A · B + ~B & Tautology ~A + ~B Complement Verify with a truth table!
Practice • Show that A + B · C = (A + B) · (A + C) is true using a truth table.
Practice • Show that A + ~A · B = A + B
Practice Simplification • Simplify A + AB + ~B and verify with a truth table
De Morgan’s Laws ~(A · B) = ~A + ~B ~A · ~B = ~(A+B) • Take a term ~A · ~B • NOT the individual members of the term A · B • Change the operator i.e. · to +, or + to · A + B • NOT the entire term ~(A+B)
De Morgan’s Law Example f = ~A · ~B + (~A + ~B) = ~~( ~A · ~B + (~A + ~B) ) NOT NOT = ~( (A + B) · ~(~A + ~B) ) De Morgan’s = ~( (A + B) · (A·B) ) De Morgan’s = ~( A·(A·B) + B·(A·B) ) Distributive = ~( A·B + A·B ) Tautology = ~(A·B) Tautology